Pengaruh Sikap, Pengetahuan, dan Norma Subjektif terhadap Niat Mahasiswa Telibat dalam Akuntansi Lingkungan - Triana Chatarinne Parabak; Grace Theresia Pontoh; Afdal (UMSurabaya Publishing, 2026)
Environmental sustainability issues show an increasing urgency in the development of educational practices and systems in the modern era. The purpose of this study is to investigate how attitudes, knowledge, and subjective norms affect students’ intention to engage in environmental accounting. This study was carried out at Hasanuddin University’s Faculty of Economics and Business using a quantitative methodology. The primary data used in this study was collected by questionnaires and subjected to PLS-SEM analysis. The study’s findings show that intentions to engage in environmental accounting are influenced by attitudes, knowledge, and subjective norms. The implication is that it is necessary to strengthen learning strategies to shape attitudes, increase understanding, and reinforce subjective norms in order to encourage students’ intentions in the field of sustainability accounting.